Analisis Novel “Bumi dan Lukanya” Karya Revianaaprl Dengan Pendekatan Pragmatik - Fani, Mulyana Mei; Nazwa, Aula; Harti, Aiga Tania; Wardani, Ayu; Chairunnisa, Chika; Rifki, Muhammad; Lubis, Fitriani (Jurnal Ilmiah Wahana Pendidikan, 2025)
The novel "Bumi dan Lukanya" by Revianaaprl tells the story of the life journey of Bumi, the main character, and covers themes of family issues, friendship, romance, and sibling relationships, all packaged well. The author skillfully conveys messages with words that touch the readers' hearts, and the story depicts events that can occur in everyday life. This novel is analyzed using a pragmatic approach, appreciating literary works based on their function to deliver and convey purposes to the readers. The aim of this research is to describe the novel "Bumi dan Lukanya" by Revianaaprl using a pragmatic approach. The method used is a qualitative descriptive method. The results of this research indicate that readers can gain values from the novel "Bumi dan Lukanya" that depict Bumi, the main character. Moreover, readers can derive deep meanings and lessons about courage, honesty, self-confidence, discipline, and fairness found in this novel. Through this novel, readers are also encouraged to appreciate the time we have in this world to avoid future regrets.